HOW TRANSFORMATIONAL LEADERSHIP EFFECT EMPLOYEE’S COMMITMENT IN BANKS - Iqbal, Faisal; Jamshaid, Fouzia; Valderrama-Plasencia, Lorenzo Rafael; Yslado-Mendez, Rosario Margarita; Gonzales-Yanac, Tatiana (The journal of contemporary issues in business and government, 2021)
Organizations have alwaysbeen in search of high caliber individuals since last few decades; however, to keep employees with distinctive capabilities committed is a matter of visionary leadership. Various studies have discovered novel ways of fabricating desired motivational levels among group members, one of those techniques which has been more viable towards employee commitment is transformational style of a figurehead. Due to financial and time restraints employees of 12 banks form private as well as public sector of Lahore city were taken as a population sample. Survey questionnaire technique was used for data collection; self-administered questionnaires were distributed among 200 bank employees with 77% response rate. Analysis of the data revealed a positive connection among transformational leadership style and employee commitment. Present study suggest a transformational leadership style as a precursor for the attainment of an elevated level of commitment which will further become accommodating towards retaining and captivating high stature employees.